Pengaruh Lingkungan Kerja, Kompensasi, dan Budaya Organisasi terhadap Loyalitas Kerja Karyawan PT Antar Lintas Sumatera di Yogyakarta - Messi Agmasari; Epsilandri Septyarini (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of the study was to determine the effect of work environment, compensation, and organizational culture on employee loyalty. Both the work environment, compensation, and organizational culture can be a major factor in the occurrence of employee loyalty in a company. The population in the study amounted to 50 people who are all employees of PT. Antar Lintas Sumatera, Yogyakarta area. Saturated sample was used as a sampling technique in this study, where a questionnaire (questionnaire) was used as a data collection technique. This research uses reliability test and validity test as instrument test. This study uses descriptive analysis, classical assumption test, normality test, multicollinearity test, and heteroscedasticity test as data analysis techniques. The t-test and f-test were used in this study as a test of linear regression analysis and hypothesis testing. The results of this study show that employee loyalty is positively and significantly influenced by compensation and work environment, while employee loyalty at PT. Between Cross Sumatra is not significantly influenced by organizational culture Keywords: Work Environment, Compensation, Organizational Culture and Employee Loyalty